Halal and Islamic tourism: Science mapping of present and future trends - Muhammad Ashraf, Fauzi; Battour, Mohamed (Emerald Publishing, 2024)
Purpose: This study aims to provide a comprehensive and systematic review of halal tourism structure using bibliometric analysis. Halal tourism interest has increased due to the high demand for tourism products adhering to Shariah law. Furthermore, the vast Muslim population has increased the demand for halal tourism products and destination factors in this niche tourism segment. Design/methodology/approach: A network visualization through bibliographic coupling and co-word analysis, this review presents a science mapping analysis to reveal the knowledge structure of emerging and future trends in halal tourism. Findings: The current and emerging trends demonstrate three themes: the fundamentals of halal tourism, communication via word of mouth in halal tourism and Muslim tourist satisfaction and loyalty. At the same time, the co-word analysis presents the four themes primarily associated with halal tourism challenges: tourist satisfaction, service quality and Muslim travellers’ attraction. Research limitations/implications: The findings serve as crucial implications, contributing to halal and general tourism theory and application. Originality/value: This review serves as crucial fundamental knowledge for future studies in halal tourism and its relevant themes for further development in tourism management. The most significant emerging theme in halal tourism is the intervention needed to increase Muslim tourist satisfaction and loyalty through halal-friendly service, customer-service quality, foods and beverages, facilities and privacy. The co-word analysis suggests increasing tourists’ engagement in halal tourism by invigorating the religiosity domain among tourists, improving service quality and perceived value and discovering new Muslim-friendly attractions. The most crucial finding from this study is to ensure that halal and Muslim-friendly tourism are at the same level, to the extent of better service according to Islamic practice. This approach would elevate the value and status of halal tourism as a trending product in Muslim and non-Muslim markets.